Pre-marital Sexual Behaviour in Student Dating: A Literature Review - Ilbert, Rizal; Marfuah, Dewi (KnE Life Sciences, 2021)
Students are often sexually active, but many of them delay their marriage to reach their education goals. This literature review aims to describe about premarital sexual behavior in students dating. The data was collected by Public media database with keywords:“Sexual Behaviour, Pre-marital, Student”. The inclusion criteria were students, with a romantic partner who had engaged in sexual activity, available free full text, qualitative study and published between 2014-2020. From 8 eligible journals met these criteria in the Public media database. The research indicates 7 themes concerning premarital sexual behaviour: love, disregard for virginity, considering pre-marital sex as normal, or a human right and sign of maturity, peer pressure, supporting a successful marriage, innate instinct. However, pre-marital sexual behavior can increase the risk of HIV and other sexual diseases. Hence, it is important for health workers to actively educate adolescents about reproductive health and pre-marital sex. Keywords: Pre-marital, Sexual Behaviour, Student, Dating